Improvement of Performance, Blood Profiles, Gut Health, and Immune Response of Broilers Supplemented with Chitosan, Bacillus subtilis, or Their Combination - Agusetyaningsih, I.; Kismiati, S.; Mangisah, I.; Widiastuti, E.; Wahyuni, H. I.; Yudiarti, T.; Sartono, T. A.; Sugiharto, S. (Tropical Animal Science Journal, 2024)
The study aimed to investigate the effect of supplementing chitosan, Bacillus subtilis or blends of both on broiler growth performance, immune response, biochemical variables, and intestinal ecology of broiler chickens. Two hundred and eighty day-old chicks were distributed into 4 experimental groups, including T0 (control, basal feed), T1 (basal feed + chitosan 0.1% feed), T2 (basal feed + B. subtilis 0.01% feed), and T3 (basal feed + chitosan 0.1% feed + B. subtilis 0.01% feed). Variables measurements and sample collection were conducted on day 35. The T3 did not differ from T0 and T1, but they consumed less (p≤0.05) feed than T2 chickens. Feed conversion ratio (FCR) was lower (p≤0.05) in T1 and T3 compared to T0 and T2 groups. Leukocyte counts in T2 and T3 were higher (p≤0.05) than those in T0. The T1, T2, and T3 had higher (p≤0.05) lymphocyte counts than T0. The T3 had lower (p≤0.05) low-density lipoprotein (LDL) levels than the T0 group. The T2 had higher (p≤0.05) levels of total protein and globulin than T3 and T0. Compared to T0 and T3, serum albumin levels were greater (p≤0.05) in T1 and T2. The T3 had higher (p≤0.05) duodenal villi height than that in the other groups. The T2 and T3 chicks had higher (p≤0.05) Newcastle disease titer than T0 and T1. Compared to T2 and T3, T0 and T1 showed a worse (p≤0.05) microscopic structure of jejunum. The T2 and T3 showed lower (p≤0.05) lesion score in bursa of fabricius than that in the other groups. In conclusion, the blends of chitosan and B. subtilis resulted in improved FCR, higher leukocyte and lymphocyte counts, lower LDL, higher duodenal villi height, higher Newcastle disease titer, better microscopic structure of jejunum, and lower lesion score in bursa of fabricius of broiler chickens.